Contents, forms and methods of preparing future teachers-philologists for professional activities in higher educational institutions of the Republic of Turkey - Emine, Marakly (Journal of Education, Health and Sport, 2019)
The relevance of the problem under study is determined by the analysis of world experience in the direction of training teachers-philologists, as well as the trends and prospects of the teacher's professional development, which is of interest both in theoretical-methodological and practical terms. The purpose of the article is to determine the content, forms and methods of preparing future philological teachers for professional activities in higher educational institutions of theRepublicofTurkey. Based on the analysis, the following were determined: content, forms (lectures, seminars, practical, laboratory classes, group consultations, master classes, individual consultations, independent work, work in a scientific library, educational and industrial practices) and methods (trainings, discussions, debates, business and role-playing games, brainstorming, case technologies) training.